Review on SnO2 Based Copper Nanoparticles for Sensor and Biological Applications: Green synthesis and characterization of CuO nanoparticles for electrochemical sensing and biological applications (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Copper oxide nanoparticles (CuO Nps) were blended utilizing Caesalpinia bonducella seed separate by means of a green manufactured pathway and were assessed for electrocatalytic properties via doing electrochemical discovery of riboflavin [vitamin B2 (VB2)]. The seeds of C. bonducella are known to have solid cancer prevention agent properties emerging because of the nearness of different parts, including citrulline, phytotropin, β-carotene, and flavonoids, which fill in as decreasing, balancing out, and top specialists. The blended CuO Nps were described utilizing UV–obvious spectroscopy, Fourier change infrared spectroscopy, thermogravimetric examination differential warm investigation, X-beam diffraction spectroscopy, X-beam photoelectron spectroscopy, and checking electron microscopy and further utilized as a modifier for a graphite anode surface. The cathode indicated great security and reproducibility over a time of 120 days.